A SEMIOTIC ANALYSIS OF VISUAL PUBLIC SERVICE ADVERTISEMENTS - Nurrizky Nabila (Journal of Language, Literature and Teaching, 2022)
Public service advertisement is advertisement that discuss social problems that occur in the community. Public service advertisements are designed in a multi-faceted manner in terms of concept, content, and also their meaning, to attract the attention of society. However, there are still many people who do not understand what the message is trying to convey from the advertisement. Therefore, this study aims to analyze the semiotic aspects of denotative and connotative meanings in visual public service advertisements. This study aims to identify and describe the denotative and connotative meanings contained in visual public service advertisements. This research applies qualitative method. The analysis of visual public service advertisements are using a semiotic theory by Roland Barthes, provides knowledge about everything that has a good and bad impact from a cause and effect. This knowledge is needed to be useful for people who want to achieve social welfare in their lives. Thus, the public can interpret the meaning and message of a visual public service advertisement properly and correctly.Keywords: Connotative meaning, Denotative meaning, Public service advertisement, Semiotic.